Neonatal Tactile Stimulation Alters Behaviors in Heterozygous Serotonin Transporter Male Rats: Role of the Amygdala - Roversi, Karine; Buizza, Carolina; Brivio, Paola; Calabrese, Francesca; Verheij, Michel M. M.; Antoniazzi, Caren T. D.; Burger, Marilise E.; Riva, Marco A.; Homberg, Judith R. (Frontiers in Behavioral Neuroscience, 2020)
The serotonin transporter (SERT) gene, especially the short allele of the human serotonin transporter linked polymorphic region (5-HTTLPR), has been associated with the development of stress-related neuropsychiatric disorders. In line, exposure to early life stress in SERT knockout animals contributes to anxiety- and depression-like behavior. However, there is a lack of investigation of how early-life exposure to beneficial stimuli, such as tactile stimulation (TS), affects later life behavior in these animals. In this study, we investigated the effect of TS on social, anxiety, and anhedonic behavior in heterozygous SERT knockouts rats and wild-type controls and its impact on gene expression in the basolateral amygdala. Heterozygous SERT+/- rats were submitted to TS during postnatal days 8 to 14, for 10 min per day. In adulthood, rats were assessed for social and affective behavior. Besides, brain derived neurotrophic factor (Bdnf) gene expression and its isoforms, components of glutamatergic and GABAergic systems as well as glucocorticoid-responsive genes were measured in the basolateral amygdala. We found that exposure to neonatal TS improved social and affective behavior in SERT+/- animals compared to naïve SERT+/- animals and was normalized to the level of naïve SERT+/+ animals. At the molecular level, we observed that TS per se affected Bdnf, the glucocorticoid-responsive genes Nr4a1, Gadd45β, the co-chaperone Fkbp5 as well as glutamatergic and GABAergic gene expression markers including the enzyme Gad67, the vesicular GABA transporter and the vesicular glutamate transporter genes. Our results suggest that exposure of SERT+/- rats to neonatal TS can normalize their phenotype in adulthood, and that TS per se alters the expression of plasticity and stress-related genes in the basolateral amygdala. These findings demonstrate the potential effect of a supportive stimulus in SERT rodents, which are more susceptible to develop psychiatric disorders.